The Mediating Role of Emotional Regulation on the Relationship between Mindfulness and Aggression among Correctional Officers - Estanislao, Amiel Jack; Cruz, Maria Angelic; Del Rosario, Mariel Dee; Nuqui, Elaine; Badiola, Mark Vincent; Vergara, Jerald; Parungao, Arold (Journal of Interdisciplinary Perspectives, 2025)
The study employs a quantitative approach to investigate the relationship between mindfulness and aggression, with emotional regulation as the mediating variable, among correctional officers. The researchers recruited 268 officers from the New Bilibid Prison (NBP) and Correctional Institution for Women (CIW) through a purposive sampling technique. Self-report instruments, the Five Facet Mindfulness Questionnaire (FFMQ-15), Difficulties in Emotion Regulation Scale Short Form (DERS-SF), and Brief Aggression Questionnaire (BAQ), were used to assess mindfulness, emotional regulation, and aggression levels. A mediation model was employed to analyse the data. Results indicated a significant indirect effect of mindfulness on aggression, mediated by emotional regulation (estimate = -0.406, p < .001, β = -0.2142). Specifically, higher levels of mindfulness were associated with lower levels of difficulty in emotion regulation (estimate = -0.899, p < .001, β = -0.4621). In turn, higher levels of difficulties in emotional regulation were associated with higher levels of aggression (estimate = 0.452, p < .001, β = 0.4636). In light of the study, the researchers recommend that correctional facilities collaborate with psychologists and criminologists to develop and implement mindfulness and emotional regulation programs tailored to the specific needs of correctional officers. Future researchers should focus on validating assessment tools for use with correctional officers and conducting longitudinal studies to evaluate the long-term impact of these programs. Additionally, employing mixed-method designs can further clarify the relationship between variables.